PERAN BIMBINGAN DAN KONSELING DALAM MENDUKUNG PERKEMBANGAN PESERTA DIDIK DIERA MODERN - Nisrina Luthfiya Azam; Reva Nur Aqila; Rahmi Anekasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of information technology, globalization, and social changes has brought various challenges to students in personal, social, academic, and career aspects. These conditions require educational services that not only focus on academic achievement but also on the development of students' potential and psychological well-being. This study aims to examine the role of guidance and counseling in supporting student development in the modern era. The method used is a literature review with a qualitative descriptive approach. Research data were obtained from various literature sources, including books, scientific journals, and articles relevant to the research topic. Data were analyzed using content analysis techniques through the processes of identifying, categorizing, and interpreting information gathered from various references. The findings indicate that guidance and counseling play a crucial role in students' personal and social development, academic success, career planning, and in helping students face the challenges of the digital era. Furthermore, guidance and counseling services contribute to character building, enhancing adaptability, and developing life skills required in the 21st century. Therefore, guidance and counseling services need to be continuously developed in innovative and adaptive ways to effectively address the needs of students in the modern era.